Experiential Learning Model in Improving Learning Outcomes of Christian Religious Education: Papuan Case - GAINAU, B. (International Journal of Psychosocial Rehabilitation, 2020)
Experiential learning is a learning process, a process of change that uses experience as learning media or Kolb’s Experiential Learning model (2005). The advantage of the experiential learning model is that the results can be felt by students through experience more effectively and can achieve the objectives of learning outcomes to the fullest. Some of the benefits of experiential learning models in building and enhancing group collaboration, in case studies in Papua, include: 1) developing and increasing interdependence among group members, 2) increasing involvement in problem-solving and decision making, 3) identifying and utilizing hidden talent and leadership, 4) increasing empathy and understanding among group members. Learning experience learning models for students provide increased learning outcomes where students have high enthusiasm and confidence in learning